The Implementation of Pop-Up Book Media to Enhance Students’ Learning Interest in IPAS Content at MIN 6 Padang City - Hafizd Triananda Putra; Sasmi Nelwati; Habib Khalilur Rahman (Universitas Negeri Semarang, 2025)
This study aims to describe the use of pop-up book media in increasing students’ learning interest in IPAS content at the elementary school level. This research employs a qualitative approach, which emphasizes the strength of narrative. The data collected in this study are descriptive data obtained through observation, interviews, and documentation. The focus of this research is to describe the implementation of pop-up book media to enhance students’ learning interest in IPAS content. The results indicate that pop-up book media contributes to improving the quality of IPAS learning in elementary schools. Pop-up book media has many advantages that support the learning process and particularly enhance students’ learning interest. The conclusion of this study is that pop-up book media can serve as an effective alternative learning medium to increase students’ learning interest in IPAS subjects.